1977
DOI: 10.1111/j.1365-3113.1977.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of variation in the stag beetle Lucanus cervus (L.) (Coleoptera: Lucanidae)

Abstract: Variation in external dimensions of Lucunus cervus (L.) has been studied using 573 specimens of both sexes from one area over a period of 3 years.Allometric relationships between various parts of the body are calculated. The taxonomy of this very variable population is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 5 publications
(2 reference statements)
0
48
0
Order By: Relevance
“…Species with relatively short mandibles exhibit a steeper allometric coefficient (slope of the regression) as size increases; on the other hand, a limit for the development of such exaggerated structures is evident in species with relatively long mandibles. L. cervus males use their mandibles in male-to-male combat (Clark 1977, Lagarde et al 2005, Fremlin 2009) and major males are equipped with enlarged and more complex mandibles (Romiti et al 2015(Romiti et al , 2016. The analysis of the geographical variation of allometric trajectories allows researchers to obtain more robust conclusions about the relative investment in these SSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with relatively short mandibles exhibit a steeper allometric coefficient (slope of the regression) as size increases; on the other hand, a limit for the development of such exaggerated structures is evident in species with relatively long mandibles. L. cervus males use their mandibles in male-to-male combat (Clark 1977, Lagarde et al 2005, Fremlin 2009) and major males are equipped with enlarged and more complex mandibles (Romiti et al 2015(Romiti et al , 2016. The analysis of the geographical variation of allometric trajectories allows researchers to obtain more robust conclusions about the relative investment in these SSC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in studying the exaggerated rostrum of the New Zealand giraffe weevil Lasiorhynchus barbicornis (Fabricius, 1775), Painting et al (2014) linked the latitudinal cline in body size with allometry (sensu Huxley and Teissier 1936). The European stag beetle, Lucanus cervus (Linnaeus, 1758), like many other species of Lucanidae, shows remarkable sexual dimorphism in mandible size and shape (Franciscolo 1997) and a great variation amongst males for this characteristic (Clark 1977, Harvey et al 2011, Hardersen et al 2011, Romiti et al 2015. The mandibles of L. cervus males can be considered as secondary sexual characteristics (SSC) that are used as weapons in intra-sexual combats (Darwin 1871, Arrow 1951, Mathieu 1969, Otte and Staymen 1979, Lagarde et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Such variation in males is often discontinuous and males are either large or small with respect to their horn or mandible size (Inukai, 1924;Clark, 1977;Eberhard, 1982;Goldsmith, 1985;Cook, 1987;Rasmussen, 1994;Siva-Jothy, 1987;Eberhard & Gutierrez, 1991;Kawano, 1995Kawano, , 1997Iguchi, 1998;Emlen & Nijhout, 2000;Moczek & Emlen, 2000;Shiokawa & Iwahashi, 2000;Tatsuta et al, 2001Tatsuta et al, , 2004. Recently, however, Rowland & Emlen (2009) indicated that several families of the Coleoptera (e.g., Scarabaeidae and Lucanidae) considered to be male dimorphic actually contain species that are trimorphic in terms of their horns or mandibles.…”
Section: Introductionmentioning
confidence: 99%
“…by plotting the relationship between body size on the x axis and the trait of interest on the y axis for a large number of individuals of the same age group or life-history stage (Cock, 1966;Emlen & Nijhout, 2000). Static allometries are commonly used to quantify patterns of morphological variation in natural populations (Clark, 1977;Goldsmith, 1985;Wenzel, 1992;Ito et al, 1994;Kawano, 1995a), to infer ecological and evolutionary processes in nature (Gould, 1973;Feener et al, 1988;Petrie, 1988Petrie, , 1992Green, 1992;Kawano, 1995bKawano, , 1997Simmons & Tomkins, 1996;Simmons et al, 1999;Emlen & Nijhout, 2000;Palestrini et al, 2000), and for comparative taxonomic purposes (Bocquet, 1953;Kermack, 1954;Kurte n, 1954Kurte n, , 1964Mitra, 1958;BaÈ hrens, 1960). While the morphological variation between individuals, on which many static allometries are based, is known to be in part due to environmental influences, certain parameters of a static allometry itself, such as its slope or the location of a switch point, are generally assumed not to depend on environmental conditions but to be constant and diagnostic for a particular species or population.…”
Section: Introductionmentioning
confidence: 99%